A Link between Psychopathy Affect and Instrumentality in Homicide. Issue 3 (August 2022) - Sohn, Ji Seun; Raine, Adrian; Hong, Young-Oh
This study tests the hypothesis that psychopathy is more associated with instrumental homicides than mixed and reactive homicides, and explores relationships between Psychopathy Checklist-Revised (PCL-R) facet/item scores and different forms of homicide: instrumental ( n = 130), mixed ( n = 103), and reactive ( n = 219) homicides. Instrumental homicides scored higher on facet 2 ( p < .01) but scored lower on facet 4 ( p < .1) compared to reactive homicides, whereas no facet scores differed between mixed and reactive homicides. Among the items of facet 2 (affective), remorselessness (item 6), and callousness (item 8) were predictive of instrumental homicide.